Analisis Pengaruh Tingkat Inflasi, Tingkat Suku Bunga SBI, dan Nilai Tukar Rupiah Terhadap Indeks Harga Saham Gabungan Bursa Efek Indonesia (BEI) Periode 2016 – 2019 - Yulianah Yulianah; Muhammad Agus Salim; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe purpose of this study was to determine how the effect of inflation, interest rates, and the rupiah exchange rate on the composite stock price index. The population in this study were all state macroeconomic data, namely data on inflation, interest rates, and exchange rates as independent variables and IHSG as the dependent variable. The samples taken are monthly data from each variable, namely inflation, interest rates, and exchange rates, and the composite stock price index January 2016 to December 2019. The results of this study indicate that partially inflation and interest rates have a significant negative effect on the stock price index. combined, the exchange rate has a significant positive effect on the composite share price index and simultaneously all independent variables have a significant effect on the composite share price index. Keywords: inflation, interest rates, and exchange rates: composite stock price index